Pelarutan Besi Selektif pada Korosi Baja Karbon dalam Larutan Buffer Asetat, Natrium Bikarbonat - CO2 Jenuh - Bunbun Bundjali; N. M. Surdia; Oei Ban Liang; Bambang Ariwahjoedi (Institute for Research and Community Services (LPPM) ITB, 2006)
This work has investigate conditions which allow pitting corrosion of carbon steel in acetate buffered test solutions of pH 3.82, 4.12, 5.12 and 6.12, 0.2 M NaOAc and standard brine solutions, all of which contains 100 mg/L sodium bicarbonate and saturated with CO2. Corrosion rates is determined by corrosion wheel and corrosion bubble tests, while surface morphology is observed by electron microscopy (SEM) and metallographic optical microscopy, whereas surface deterioration as well as corroded lattice structure of the steel is monitored through measurements by X-ray Diffraction (XRD) patterns. The X-ray Diffraction Patterns of corroded carbon steel in any of the above test solutions exhibit a decrease in relative intensity of 110 and 200 lattice planes and an increase in the 211 lattice plane. The extent of decrease of the diffracted X-ray intensities increases with the increase in the percentage of corroded carbon steel coupon weight loss. This might reflect a selective dissolution of iron atoms situated in both lattice planes. It is suspected that this observation is due to the fact that 211 lattice plane has the smallest percentage of atomic occupancy among the three, thus it might have the greatest chance to be inserted with carbon atoms which in turn gives a protective effect toward iron atoms against further dissolution. Although, the corrosion process starts from the surface phase, this experiment reveals that X-ray diffraction pattern of the three lattice planes could be employed as some sort of carbon steel corrosion indicator. Consequently, corrosion inhibitor performance could be deduced from its ability to maintain diffraction pattern of the initial carbon steel specimen.